Hubungan Umur, Jenis Kelamin dan Masa Kerja dengan Keluhan Musculoskeletal Disorders (MSDs) pada Dokter, Bidan dan Perawat di RSUD Provinsi NTB - Candra Dewi, Kadek; Pebruanto, Henry; Pratiwi, Made Rika Anastasia; Suanjaya, Made Agus (Jurnal Ilmiah Wahana Pendidikan, 2024)
Background:Musculoskeletal Disorders (MSDs) is an accumulation of various types of pain in nerves, tendons and muscles that are used uncontrollably, work is done repeatedly and static work positions for long periods of time. MSDs are disorders that are rarely life-threatening, but MSDs can reduce quality of life and work productivity. This study aims to determine the relationship between age, sex and work period with complaints of MSDs among doctors, midwives and nurses at the NTB Provincial Regional Hospital. Method:This research is an analytical observational study using a research design cross sectional. The sampling technique is proportionate stratified random sampling. The research sample was 86 samples according to the inclusion and exclusion criterias. The data obtained were analyzed using a correlation test chi-square. Results:The results of this study showed that 49 people aged >30 years complained of MSDs and 17 people aged ≤30 years complained of MSDs (19.8%). There were 42 female respondents with MSDs complaints (48.8%) and 24 male respondents with MSDs complaints (27.9%). Respondents with work experience >5 years with MSDs were 37 people (30.7%) and respondents with work experience ≤ 5 years with MSDs complaints were 29 people (35.3%). There is a significant relationship between age and complaints of MSDs (p-value of 0.000;p-value < 0.05). There is no significant relationship between gender and complaints of MSDs (p-value of 0.137;p-value > 0.05). There is a significant relationship between working hours and complaints of MSDs (p-value of 0.001;p-value > 0,05). Conclusion:There is a significant relationship between age and length of service with MSDs complaints and there is no significant relationship between gender and MSDs complaints among doctors, midwives and nurses at the NTB Provincial Regional Hospital.